Social and fashion technology generation herbs from concentrate from desalination - Amaral, Rodrigo Vieira Alves; Alves, Sonáli Amaral de Lima; França, Kepler Borges; Fernandes, Maniza Sofia Monteiro; Costa, Tereziana Silva; Barbosa, Tellys Lins Almeida (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
The Social Technology comes into existence as a response to environmental deterioration and social exclusion that were caused by the dominant approaches; is a substitute concept of Appropriate Technology. The Social Technology drives social change through products and techniques. The community Uruçu, located in São João do Cariri-PB is a beneficiary of social technology through Project Water: Source of Food and Income, which functions as an alternative income for farmers. The Project: promotes the production of vegetables through hydroponics, an activity that seeks the interaction of actors in a particular location. The objective of this work is to verify the mode of production of Uruçu community can be considered a social technology. For this, a theoretical review of the concepts of social technology and hydroponics was performed, in addition to explaining the operation of the project Water: Source of Food and Income. For this it was necessary to do field research, which entailed visiting the community and interviews with participants of the same. Thus it can be concluded from the activities that are performed by deploying Water project is considered a social technology.